2018
DOI: 10.1007/s00330-017-5268-z
|View full text |Cite
|
Sign up to set email alerts
|

Are pancreatic IPMN volumes measured on MRI images more reproducible than diameters? An assessment in a large single-institution cohort

Abstract: • MRI measurements by different radiologists can be used for IPMN follow-up. • Both diameter and volume measurements demonstrate excellent interobserver and intraobserver reproducibility. • Manual axial measurements show the highest interobserver reproducibility in determining size. • Axial and coronal volume measurements show similar limits of agreement. • Manual axial measurements show the lowest variability in agreement range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Moreover, the IPMN's segmentation process was performed manually, based on a "by-pen" tracing method on paper that eventually was scanned and digitalized, rendering this method not feasible for routine clinical practice. Our semi-automatic segmentation method is more practical, although not correlated to the grade of dysplasia, and volumetry may potentially be performed with any segmentation tool available in any PACS system in a non-time-consuming fashion as proposed by Pandey P. et al [12]. Furthermore, semi-automatic volumetric segmentation has the important advantage of being independent of the axis manually chosen by the radiologist and has very high intra-and interobserver reproducibility even in smaller lesions [12,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the IPMN's segmentation process was performed manually, based on a "by-pen" tracing method on paper that eventually was scanned and digitalized, rendering this method not feasible for routine clinical practice. Our semi-automatic segmentation method is more practical, although not correlated to the grade of dysplasia, and volumetry may potentially be performed with any segmentation tool available in any PACS system in a non-time-consuming fashion as proposed by Pandey P. et al [12]. Furthermore, semi-automatic volumetric segmentation has the important advantage of being independent of the axis manually chosen by the radiologist and has very high intra-and interobserver reproducibility even in smaller lesions [12,17].…”
Section: Discussionmentioning
confidence: 99%
“…Our semi-automatic segmentation method is more practical, although not correlated to the grade of dysplasia, and volumetry may potentially be performed with any segmentation tool available in any PACS system in a non-time-consuming fashion as proposed by Pandey P. et al [12]. Furthermore, semi-automatic volumetric segmentation has the important advantage of being independent of the axis manually chosen by the radiologist and has very high intra-and interobserver reproducibility even in smaller lesions [12,17]. Thus, it may potentially overcome the issue of nonstandardized manual measurements of cystic diameters, which are affected by intra-and inter-observer variability [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies by Pandey et al and [12] Jeon et al [14] showed reproducible size measurements of pancreas in MRI, however, not in CF patients but in patients with intraductal papillary mucinous neoplasm (IPMN), non hypervascular pancreatic neuroendocrine tumor (PNET) and pancreatic ductal adenocarcinoma (PDAC).…”
Section: Discussionmentioning
confidence: 99%
“…A 6C1 HD transducer at 1.5 to 6.0 MHz was used for the B-Mode ultrasound and elastography. Diagnosis of pancreatic lipomatosis was made when the pancreas was significantly more echogenic than the adjacent liver parenchyma [12]. The pancreas was measured standardized at the head, body, and tail in concordance to current literature [10, 13].…”
Section: Main Textmentioning
confidence: 99%